A Social–Ecological System Approach to Analyze Stakeholders’ Interactions within a Large-Scale Rangeland Restoration Program - Petursdottir, Thorunn; Arnalds, Olafur; Baker, Susan Catherine; Montanarella, Luca; Aradottir, Asa (Ecology and Society, 2013)
Large-scale restoration projects are normally part of a complex social–ecological system where restoration goals are shaped by governmental policies, managed by the surrounding governance system, and implemented by the related actors. The process of efficiently restoring degraded ecosystems is, therefore, not only based on restoring ecological structure and functions but also relies on the functionality of the related policies, the relevant stakeholder groups, and the surrounding socioeconomic and political settings. In this research, we investigated the SES of rangeland restoration in Iceland to estimate whether social factors, such as stakeholders’ attitudes and behavior, can be used to evaluate the effectiveness of agri-environmental policies on rangeland restoration and improved land management. We used qualitative approaches, interviewing 15 stakeholders. Our results indicate that social factors such as attitude toward restoration and land management practices can be used as indicators to evaluate the effectiveness of restoration policies. They also strongly indicate that lack of functionality in the governance system of social–ecological systems can reduce the desired progress of policies related to large-scale natural resource management projects, such as rangeland restoration, and possibly halt the necessary paradigm shift among stakeholders regarding improved rangeland management.